Hubungan antara Gaya Hidup Sehat dengan Tingkat Stres Siswa Kelas XII SMA Negeri di Denpasar Menjelang Ujian Nasional Berdasarkan Strategi Coping Stres - Wibawa, Nyoman Adi Krisna; Widiasavitri, Putu Nugrahaeni (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2013)
National examination is a standard passing score that has been set by the government to meet national educational competencies. Students who implant the positive values to healthy lifestyle in their daily lives, it will be able to manage themselves with appropriate coping strategies to get out of stressful situations that push. Quantitative research with regression analysis method aimed to see the relationship between healthy lifestyle with stress level of twelfth grade students of high school in Denpasar towards final examination based on stress coping strategy, like problem focused coping and emotion focused coping. Sampling technique uses cluster random sampling with 317 subjects of twelfth grade students in Denpasar. Measuring instrument in this study is the healthy lifestyle scale (reliability 0.846), stress level scale (reliability 0.913), and stress coping strategies scale (reliability 0.868). Z-score test and regression analysis were used to divide into groups with 143 subjects coping strategies in problem focused coping (p<0.05) with a regression equation Y=75.018-0.556X while on emotion focused coping were 112 subjects (p<0.05) the regression equation Y=88.748-.440X, then there is a relationship between a healthy lifestyle in problem focused coping strategies group and emotion focused coping with stress levels at high school students especially for twelfth grade before the National examination. Score of R correlation on group problem focused coping is 0.876 and the group emotion focused coping is 0.844. Then the relationship between a healthy lifestyle and stress levels in group problem focused coping strategies and emotion focused coping belong to strongest relationship between the two groups (problem and emotion focused coping). Uses problem focused coping more efecctive than emotion focused coping to see the relationship between healthy lifestyle with stress level of twelfth grade students of high school in Denpasar towards final examination. Keywords: stress levels, a healthy lifestyle, coping strategies, the National examination